Efficacy of a Cyperus rotundus extract and antibiotics on bacteria isolated from urinary tract infections - Mohammed, Hala R.; Sabbar, Rusul; Jawad, Yaqeen; Makki Al-Hindy, Hayder Abdul-Amir (Pharmakeftiki, 2025)
Urinary tract infection (UTI), an inflammatory condition resulting from pathogenic invasion of the urinary tract, remains a prevalent clinical concern. This study aimed at isolating common uropathogenic bacterial strains from urine samples collected from patients attending consultation clinics at the Al-Imam Sadeq and the Al-Hilla Teaching Hospitals (Iraq) between October and December 2024. The objectives were twofold: (i) to evaluate the antimicrobial susceptibility profiles of the isolated strains, and (ii) to assess the antibacterial efficacy of Cyperus rotundus extract (CRE). The findings demonstrated that CRE at a concentration of 1,000 µg/mL inhibited the growth of Escherichia coli and Pseudomonas aeruginosa, alongside other locally isolated bacterial species. The minimum inhibitory concentration (MIC) of CRE was determined to be 62.5 µg/mL. Notably, E. coli and P. aeruginosa exhibited susceptibility to all tested antibiotics, whereas Proteus mirabilis showed resistance to all agents. Additional isolates, including Staphylococcus spp. and Enterococcus faecalis, displayed variable susceptibility patterns, with E. faecalis being sensitive to certain antibiotics and resistant to others.